Transformation of the 3 kg Liquefied Petroleum Gas (LPG) Subsidy Policy in Indonesia - Elmi Wahyuni; Budiman Rusli; Candradewini Candradewini (Yayasan Ilomata, 2026)
The transformation of Indonesia’s 3-kg LPG subsidy policy marks a progressive shift from an open, commodity price–based distribution system toward a beneficiary-targeted scheme reinforced by digital infrastructure. This study examines the evolution of policy objectives and governance arrangements across the LPG supply chain, spanning the 2007 kerosene-to-LPG conversion program through the post-2024 adoption of National Identification Number (NIK)–based targeting and digital transaction recording. Departing from earlier research that primarily addresses fiscal costs or subsidy effectiveness, the analysis advances a structured periodization framework integrated with a supply-chain governance perspective to illuminate how regulatory reforms, targeting instruments, and digital systems jointly reshape delivery mechanisms. Employing a descriptive qualitative design grounded in historical-archival methods, the study draws on government regulations, official reports, statistical records, and scholarly literature. Three analytically distinct phases emerge. The first phase (2007–2018) established an open distribution model that successfully curtailed kerosene use and generated fiscal savings, yet suffered substantial leakage and targeting inaccuracies. The second phase (2019–2023) constituted a transitional period characterized by strengthened regulatory frameworks and nascent digital monitoring. The third phase (2024–present) institutionalizes identity-based distribution through NIK verification and digital applications that document transactions throughout the supply chain, thereby enhancing accountability and precision. By combining policy periodization with a supply-chain governance lens, the study provides an analytical framework for understanding the institutional evolution of subsidy delivery. Persistent challenges remain, including inclusion errors, ambiguous beneficiary criteria, unclear consumption quotas, and ongoing vulnerability of the distribution chain to price distortions.